Restoration of permanent preservation areas: a case study in the city of Maringa (PR) - Albertin, Ricardo Massulo; Angelis, Bruno Luiz Domingos De; Angeoletto, Fabio Henrique Soares; Silva, Frederico Fonseca; Baggio, Marina Moura; Traci, Daniela Ferreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The negative environmental impacts caused by human activities have consequences that compromise the quality of life in cities.One way to minimize is through the institutionalization of permanent preservation areas.Thus, this study aimed to diagnose and establish guidelines and procedures for the recovery of permanent preservation areas in Bandeirantesdo Sul Creek,in the city of Maringa, Parana State(Brazil).The methodological procedures contemplated the steps of characterization of the study area, on-site surveys and restoration of permanent preservation areas as environmental legislation and in CarpanezzieCarpanezzi (2006) according to the principle of choice, selection and combination of species in the bioclimatic region 4.The resultsshowed the Bandeirantes do Sul Creek is partially degraded, with the occurrence of sedimentation processes and fluvial erosion, due, among other things, the absence of native vegetation and the presence of exotic species that compromise biodiversity.The area actually to be recomposed with native species totaled 14,620.71m² in which provision is made for the planting of 1,675 native trees